2013
DOI: 10.1176/appi.ajp.2012.12070908
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSK-3β Genetic Variation With GSK-3β Expression, Prefrontal Cortical Thickness, Prefrontal Physiology, and Schizophrenia

Abstract: OBJECTIVE Glycogen synthase kinase 3β (GSK-3β) is an enzyme implicated in neurodevelopmental processes with a broad range of substrates mediating several canonical signaling pathways in the brain. The authors investigated the association of variation in the GSK-3β gene with a series of progressively more complex phenotypes of relevance to schizophrenia, a neurodevelopmental disorder with strong genetic risk. METHOD Based on computer predictions, the authors investigated in humans the association of GSK-3β func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Furthermore, we also found that individuals carrying the T allele in both genes also have lower behavioral accuracy during working memory in a large sample of healthy subjects. Previous studies have indicated that genetic variability in healthy subjects drives variation in prefrontal activity (Blasi et al, 2013b;Huffaker et al, 2009) and lowers behavioral performance (Goldberg et al, 2003). All together, these findings are reminiscent of results in patients with schizophrenia (Callicott et al, 2000), and they have been interpreted as the need for greater recruitment of cortical resources to perform the task with reduced or similar behavioral proficiency (Bertolino and Blasi, 2009a;Manoach, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we also found that individuals carrying the T allele in both genes also have lower behavioral accuracy during working memory in a large sample of healthy subjects. Previous studies have indicated that genetic variability in healthy subjects drives variation in prefrontal activity (Blasi et al, 2013b;Huffaker et al, 2009) and lowers behavioral performance (Goldberg et al, 2003). All together, these findings are reminiscent of results in patients with schizophrenia (Callicott et al, 2000), and they have been interpreted as the need for greater recruitment of cortical resources to perform the task with reduced or similar behavioral proficiency (Bertolino and Blasi, 2009a;Manoach, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genetically induced levels of 5-HT2A receptors may in turn interact with lower or greater expression of D2L postsynaptic receptors as a function of DRD2 variation in determining differential levels of stimulation of prefrontal pyramidal neurons or interneurons of relevance for cognitive processing. Another synergistic or alternative mechanism of the combined effect of rs1076560 and rs6314 on working memory processing is that stimulation of D2 and 5-HT2A receptors implicates intraneuronal adjustments that modulate common pathways including molecules such as AKT1 and GSK3beta (Beaulieu, 2012;de Bartolomeis et al, 2013), whose expression and related genetic variation have been associated with schizophrenia (Blasi et al, 2011(Blasi et al, , 2013bTan et al, 2008). In line with the relevance of common signaling cascades, current evidence also suggests that the cross-talk between D2 and 5-HT2A may be facilitated by the assembly of heteromers (Albizu et al, 2011;de Bartolomeis et al, 2013;Fuxe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal brains of this collection were excluded from the analysis because of their limited sample size (http:// braincloud.jhmi.edu/). Details of informed consent, ethics, autopsy, tissue acquisition, handling processing, dissection, clinical characterization, diagnoses, neuropathological examinations, toxicological analysis, RNA extraction, quality control measures, and DNA evaluation from cerebellar tissue were described previously (Colantuoni et al, 2011;Blasi et al, 2013a;Blasi et al, 2013b).…”
Section: Cnr1 Mrna Expression In Postmortem Pfc Of Healthy Humansmentioning
confidence: 99%
“…All preprocessing was performed as described previously (Blasi et al, 2013b). Following preprocessing, all fMRI data were analyzed using General Linear Model (GLM) to detect changes in brain activity based on a priori task design and hemodynamic response function.…”
Section: Fmri Data Analysismentioning
confidence: 99%
See 1 more Smart Citation